The role of C-Reactive Protein in the level severity of hyperemesis gravidarum - Rosiyana, Ni Made; Arsyad, M. Aryadi; Syamsuddin, Saidah; Emilia, Ni Luh; Lilian Mua, Estelle; Sekeon, Robi Adikari; Anggreyni, Meilin; Kaluku, Suratno; Azhar, Bayu; Purwanza, Sena Wahyu (Gaceta Médica de Caracas, 2022)
Introduction: Causes of Hyperemesis Gravidarum (HG) are unknown. C-Reactive Protein (CRP) is thought to play an important role in the occurrence of HG. This study is to determine the values of CRP in normal pregnant women and hyperemesis gravidarum (HG), CRP levels on HG severity, and to know the role of CRP in the severity of HG.